Clinical consensus statement: Establishing the roles of locoregional and systemic therapies for the treatment of intermediate-stage hepatocellular carcinoma in Canada. (April 2023) - Wong, Jason K.; Lim, Howard J.; Tam, Vincent C.; Burak, Kelly W.; Dawson, Laura A.; Chaudhury, Prosanto; Abraham, Robert J.; Meyers, Brandon M.; Sapisochin, Gonzalo; Valenti, David; Samimi, Setareh; Ramjeesingh, Ravi; et al.
Highlights: The treatment landscape of intermediate-stage HCC is evolving due to developments in locoregional and systemic therapies. Consensus recommendations relevant to the Canadian context were developed using a modified Delphi approach. Statements generally reflected a shift toward greater treatment tailoring and strategies with curative intent. Abstract: Background: Hepatocellular carcinoma (HCC) a leading cause of cancer mortality worldwide and approximately one-third of patients present with intermediate-stage disease. The treatment landscape of intermediate-stage HCC is rapidly evolving due to developments in local, locoregional and systemic therapies. Treatment recommendations focused on this heterogenous disease stage and that take into account the Canadian reality are lacking. To address this gap, a pan-Canadian group of experts in hepatology, transplant, surgery, radiation therapy, nuclear medicine, interventional radiology, and medical oncology came together to develop consensus recommendations on management of intermediate-stage HCC relevant to the Canadian context. Methods: A modified Delphi framework was used to develop consensus statements with strengths of recommendation and supporting levels of evidence graded using the AHA/ACC classification system. Tentative consensus statements were drafted based on a systematic search and expert input in a series of iterative feedback cycles and were then circulated via online survey to assess the level of agreement. Results & Conclusion: The pre-defined ratification threshold of 80 % agreement was reached for all statements in the areas of multidisciplinary treatment (n = 4), intra-arterial therapy (n = 14), biologics (n = 5), radiation therapy (n = 3), surgical resection and transplantation (n = 7), and percutaneous ablative therapy (n = 4). These generally reflected an expansion in treatment options due to developments in previously established or emergent techniques, introduction of new and more active therapies and increased therapeutic flexibility. These developments have allowed for greater treatment tailoring and personalization as well as a paradigm shift toward strategies with curative intent in a wider range of disease settings.